Peningkatan Hasil Belajar Tata Surya melalui Problem Based Learning di Sekolah Dasar - Winda Nuraisyah; Kusniah; Ahmad Budiwan Halimi; Viki Fahril Arfandi; Ivon Ayunatasari Maimunah Albay; Anang Sumarno; Moh. Wari Wahyuni; Alfarisi Ahmad; Moh. Ainur Rahman (Action Research Journal, 2026)
This study aims to improve the learning outcomes of 6B grade students at SDN Pandian 1 Sumenep on the Solar System topic through the implementation of the Problem Based Learning (PBL) model. This study employs a Classroom Action Research (CAR) method conducted over two cycles. The research subjects were 30 students of class 6B in the 2025/2026 academic year. The instruments used included Student Worksheets (LKPD) and individual written tests. Results showed a significant improvement from Cycle 1 to Cycle 2. In Cycle 1, the class average was only 63.67, with most students still in the sufficient category. In Cycle 2, the group LKPD average rose to 95.57, and the individual written test average reached 83.57. These findings indicate that the PBL model is effective in enhancing students' understanding of the solar system, planet sequences, characteristics, and classification. It is concluded that the application of the Problem Based Learning model can improve the IPAS learning outcomes of 6B grade students at SDN Pandian 1 Sumenep